Seletividade de inseticidas alternativos a Telenomus podisi Ashmead (Hymenoptera: Scelionidae) - Smaniotto, Lisonéia Fiorentini (2011)
The aim of this study was to verify the selectivity of alternative insecticides to the egg parasitoid, Telenomus podisi (Ashmead) (Hymenoptera: Scelionidae). The following products were evaluated: Compostonat, Natuneem, Natualho, Geranium Oil, Pironat and Rotenat. A quantity of 0.2 ml of each product, at the manufacturer’s recommended concentration, was sprayed onto cards (1.0 × 5.0 cm) supporting the eggs of Euschistus heros (Fabricius) (Hemiptera: Pentatomidae). The control was sprayed with distilled water. In this test, it was available the parasitism rate, emergency of percentage, adults longevity, period of adult-egg, sexual ration of the emerged parasitoids. It was verified that in the test with chance of choice, the alternative insecticides Compostonat, Natualho and Geranium oil affect the rate of parasitism. In the test with no-chance of parasitism choice the rate of parasitism was affected by the alternative insecticides Rotenat in the post-parasitism, Natualho and Geranium oil in the pre-parasitism, while the emergency was reduced by Compostonat and Geranium oil in the pre-parasitism. The parameter period adult-egg was affected by the products Natualho in pre-parasitism for females and Geranium oil in the post-parasitism for male, the sexual ration was reduced by Natualho and Geranium oil in the post-parasitism. The longevity was reduced by alternative insecticides Rotenat and Geranium oil in the pre-parasitism, and elevated by Geranium oil in the post-parasitism. Thus, Natuneem was the unique product to present selectivity to T. podisi in all the available parameters, although the other alternative insecticides are no selective, basing in the tests hear realized, because they affected the majority of the available parameters, compromising the control of prague- insect.